PERBANDINGAN MODEL LATIHAN PEREGANGAN STATIS DAN DINAMIS TERHADAP FLEKSIBILITAS - Aditya Permana Putra; Sudirman Husin; Suranto Suranto (JUPE (Jurnal Penjaskesrek), 2016)
This study aimed to determine how much the comparation of exercise model static stretching anddynamic stretching. Methodology used in this study was experiment. Data analysis technique using a single variance analysis technique. In the model of static stretching exercise it can count that tcount = 8.765 ttable = 2.042 which means rejacted (H0) so theres an influence of static stretching exercises model. In model of dynamic stretching exercises tcount = 3.041 ttable = 2.042, then rejacted the null hypothesis (H0) that there was ab effect of stretching models dynamic. While the analysis of the final test model group differences static stretching exercises and dynamic obtained tcount = 3.041 ttable = 2.042 so that there are differences between groups of static and dynamic stretching exercises model for flexibility.Penelitian ini bertujuan untuk mengetahui seberapa besar perbandingan model latihan peregangan statis dan model peregangan dinamis. Metodologi yang digunakan dalam penelitian ini adalah eksperimen. Teknik analisis menggunakan teknik analisa varians tunggal. Pada model latihan peregangan statis didapat thitung 8,765 ttabel = 2,042 yang berarti tolak ( H0 ) sehingga ada pengaruh model latihan peregangan statis. Pada model latihan peregangan dinamis didapat thitung 3,041 ttabel = 2,042 maka tolak hipotesis nol ( H0 ) sehingga ada pengaruh model peregangan dimanis. Pada analisis perbedaan tes akhir kelompok model latihan peregangan statis dan dinamis didapat thitung 3,041 ttabel = 2,042 sehingga ada perbedaan yang antara kelompok model latihan peregangan statis dan dinamis terhadap fleksibilitas.Kata kunci: dinamis, fleksibilitas, peregangan statis